PCSK9 inhibition: from effectiveness to cost-effectiveness - Mercep, Iveta; Strikic, Dominik; Hrabac, Pero; Pecin, Ivan; Reiner, Željko (Frontiers in Cardiovascular Medicine, 2024)
Dyslipidaemia is a complex disorder characterised by abnormal lipid levels in the blood, including cholesterol and triglycerides, and plays an important role in the development of atherosclerotic cardiovascular disease (CVD). Most risk factors for cardiovascular disease are modifiable, and dyslipidaemia is a key factor among them. It can result from a combination of genetic and environmental factors. A distinction is made between primary dyslipidaemia, which is mainly caused by inherited genetic changes, and secondary dyslipidaemia, which is due to underlying diseases or certain medications. The treatment of dyslipidaemia has evolved over the years. In the past, statins were the first choice, but newer drugs such as PCSK9 inhibitors have gained prominence due to their effectiveness in lowering lipids. Although recent guidelines recommend PCSK9 inhibitors for high-risk patients and patients who cannot tolerate statins, their widespread use is limited due to cost. Several meta-analyses have confirmed the efficacy and safety of PCSK9 inhibitors and have shown a significant reduction in LDL cholesterol levels. However, the long-term side effects and interactions with other risk factors for cardiovascular disease remain uncertain. In addition, cost-effectiveness analyses have shown mixed results, with some countries considering PCSK9 inhibitors cost-effective for certain patient groups, while others consider them less economical. Meanwhile, initial data from patients using PCSK9 inhibitors support the results of the clinical trials. To summarise, PCSK9 inhibitors represent a revolutionary solution for lowering LDL cholesterol, but their cost-effectiveness remains controversial. Despite the controversy, they offer clear benefits for high-risk patients and should therefore be considered in the treatment of dyslipidaemia.